A Study on Evaluating the Impact of Green Marketing on Sustainable Growth and Development in Serbia SME’s Sector: A Moderating Role of Ecopreneurship - Atif Aziz Aziz (Arthatama, 2020)
The research evaluated the impact of green marketing on sustainable growth and development where the case of the Serbian SME sector was specifically considered. In addition, the research aimed to determine the moderating role of ecopreneurship between green marketing and sustainable growth and development. The research was quantitative, and the data was gathered using a survey questionnaire that was close-ended and based on 5-points Likert scale. The analysis was conducted on SmartPLS, and the sample size considered was 450 participants belonging to the SME sector of Serbia. The statistical technique employed for the analysis was Structural Equation Modelling (SEM). The findings revealed that overall, the effect of green marketing on the Serbian SMEs was statistically significant, whereas ecopreneurship’s moderation was also found to be significant between green marketing and sustainable growth and development. Specifically, government legislation, consumer behaviour and the attitude of senior managers affected sustainable growth and development significantly. The research was limited to Serbia; therefore, it cannot be generalized to other countries. In addition, the research was limited to the SME sector.